Internationalisation of MNCs from developing economies: Case of Malaysia - Ahmad, Syed Zamberi; Hashim, Fariza (World Business Institute, 2007)
Internationalisation is a process that MNCs have to engage in becoming global players. This process enables them to be mature in their operations in foreign markets and strengthen their competitive position abroad. The current trend has witnessed the surge of MNCs not only from developed nations but also from developing nations that actively involve in the global economy. The process of internationalisation take place among MNCs from developed economies are also experienced by firms from developing economies, however the pattern of the process is slightly different.This study explored the internationalisation process of MNC from Malaysia, namely TM Berhad, a leading telecommunication company in the country. Its motives, expansion strategies and entry mode chosen in setting up its operations abroad are deeply analyzed. This study discovered that internationalisation process that Malaysian firm experienced is not similar to the internationalisation process that are discussed in the literature which were based on firms from developed economies. TM as a government linked firms internationalise by utilizing its ownership advantages as other MNCs, but the efforts were more driven by opportunities and government linkages rather than other factors.